Effect of cumulated dose on hydrogen emission from polyethylene irradiated under oxidative atmosphere using gamma rays and ion beams. (January 2016) - Ferry, M.; Pellizzi, E.; Boughattas, I.; Fromentin, E.; Dauvois, V.; de Combarieu, G.; Coignet, P.; Cochin, F.; Ngono-Ravache, Y.; Balanzat, E.; Esnouf, S.
Abstract: This work reports the effect of very high doses, up to 10 MGy, on the H2 emission from high density polyethylene (HDPE) irradiated with gamma rays and ion beams, in the presence of oxygen. This was obtained through a two-step procedure. First, HDPE films were pre-aged, at different doses, using either gamma rays or ion beams. In the second step, the pre-aged samples were irradiated in closed glass ampoules for gas quantification, using the same beam type as for pre-ageing. The hydrogen emission rate decreases when dose increases for both gamma rays and ion beams. However, the decreasing rate appears higher under gamma rays than under ion beam irradiations and this is assigned to a lesser oxidation level under the latter. Herein, we show the effectiveness of the radiation-induced defects scavenging effect under oxidative atmosphere, under low and high excitation densities. Highlights: Polyethylene is radio-oxidized, using gamma rays and ions beams. H2 emission rate is determined as function of dose and irradiation type. H2 emission rate is observed to decrease when dose increases. H2 decrease is attributed to energy and radical transfers to oxidized defects.